Konseptualisasi Untuk Komunitas: Menuju Kesukarelaan Dalam Aksi Adaptasi Dan Mitigasi Bencana - Syahrizal Koem; Noviar Akase (Universitas Negeri Gorontalo, 2022)
Understanding the concept of community resilience is important, as an effort to increase public sensitivity to the impacts caused by disasters. In this aspect, local communities, especially young people, can increase their adaptive capacity, become more resilient, and take a bigger role in achieving local prosperity. The program aims to address the gaps in the concept of disaster for local communities, which focuses on increasing community understanding and capacity so that communities can voluntarily undertake adaptation and mitigation measures. Community forums are an important component in achieving the target of this program. Community forums formed include PRB and TSBM forums. The presence of community forums is a pillar in building and increasing community resilience. This requires adequate support so that the forum as a local organization can make a real contribution. The sustainability of the disaster management training program still needs to be developed, in collaboration with community organizations to ensure resilience capacity is maintained. The implementation of this program can provide a stimulus to local governments and the community about the importance of understanding the concept of disaster to the community, in order to create a sense of responsibility and empathy within the local community.